Prediction of expected genetic gain in progeny test of Samama [Anthocephalus macrophyllus (Roxb.) Havil.] in West Seram District, Maluku Province, Indonesia - Ambar Dwi Suseno; Yossa Istiadi; Sata Yoshida Srie Rahayu (Universitas Pakuan, 2021)
The research objective is to find out genetic variation, estimated heritability value and the expected genetic gain of Samama [Anthocephalus macrophyllus (Roxb.) Havil.] on variation in stem diameter and plant height as superior seed producers. The research was conducted in Uraur Village, West Seram Regency, Maluku Province. The trials consisted of 80 families. All of the trials were laid out in randomized complete block designs (RCBD), 4-trees plots with 4 replications (blocks) at spacing of 5m×2m. Data collection was carried out for 2 months (February to March 2020) and was focused on observing growth variations and genetic parameters in the progeny trial block at 4 years of age including plant height and diameter at breast height. The results of this study indicate that there are variations in growth, where the Anova test results show very significant differences in the plant height parameters namely Family (F = 3.417 p 0.01), Block (F = 437.465 p 0.01) and Family and Block Interactions (F = 3.351 p 0.01). The stem diameter parameters also showed very significant differences, namely Family (F = 2.785 p 0.01), Block (F = 353.095 p 0.01) and Family and Block Interaction (F = 2.611 p 0.01). The value of family heritability and individual heritability on plant height characters belonged to a high category with a family heritability value of 0.7213 and individual heritability value of 0.8811, while the stem diameter character for individual heritability was high with a value of 0.4406 but family heritability was moderate with value of 0.5204. The value of genetic correlation was high and positive and generally shows a greater value than the phenotypic correlation. Genetic correlation values ranged from 0.967 while phenotypic correlation values ranged from 0.8944. The highest selection priority was found in the height of the stem with a weight constant of 0.239. Predicted expected genetic gain was 3.0% for diameter parameter and 3.2% for height parameter.Objektif dari penelitian ini adalah menemukan variasi genetik, taksiran nilai heritabilitas serta peluang perolehan expected genetic gain tanaman Samama [Anthocephalus macrophyllus (Roxb.) Havil.] pada variasi diameter dan tinggi pohon sebagai penghasil benih unggul. Penelitian dilakukan di Desa Uraur Kabupaten Seram Bagian Barat Provinsi Maluku. Percobaan ini menggunakan 80 famili. Penelitian ini dibangun dengan desain randomized completely block design (RCBD), jarak tanam 5 x 2 m, 4 ulangan (blok) dan 4 treesplot. Pengumpulan data dilakukan selama 2 bulan (Februari sampai dengan bulan Maret 2020) memfokuskan pada pengamatan variasi pertumbuhan dan parameter genetik yang berada di blok uji keturunan pada umur 4 tahun meliputi tinggi dan diameter setinggi dada. Hasil Penelitian ini menunjukkan bahwa terdapat variasi pertumbuhan, dimana dari hasil uji Anova menunjukkan perbedaan sangat nyata pada parameter tinggi yaitu Famili (F=3,417 p0,01), Blok (F=437,465 p0,01) dan Interaksi Famili dan Blok (F=3,351 p0,01). Pada parameter diameter juga menunjukkan perbedaan sangat nyata yaitu Famili (F=2,785 p0,01), Blok (F=353,095 p0,01) dan Interaksi Famili dan Blok (F=2,611 p0,01). Nilai heritabilitas famili dan heritabilitas individu pada karakter tinggi tanaman memiliki kategori tinggi dengan nilai heritabilitas famili 0,7213 dan nilai heritabilitas individu 0,8811, sedangkan pada karakter diameter tanaman untuk heritabilitas individu tergolong tinggi dengan nilai sebesar 0,4406 namun heritabilitas famili tergolong sedang dengan nilai 0,5204. Nilai korelasi genetik bernilai tinggi dan positif serta secara umum menunjukkan nilai yang lebih besar dibandingkan dengan korelasi fenotipik. Nilai korelasi genetik berkisar 0,967 sedangkan nilai korelasi fenotipiknya berkisar 0,8944. Prioritas seleksi tertinggi ditemukan pada tinggi batang dengan nilai konstanta bobot sebesar 0,239. Prediksi expected genetic gain diperoleh 3,0 % untuk parameter diameter dan 3,2 % untuk parameter tinggi.